A Year of Sustainable Developments. Issue 1 (28th December 2022) - Smith, David J.
Abstract : Sustainability in the spotlight : ChemSusChem Editor in Chief David Smith introduces the new volume of the journal and looks back over the last twelve months and ahead to the coming year, as well as introducing a new Chair of the ChemSusChem Editorial Board and the journal's first Early Career Advisory Board.